2020
DOI: 10.3390/jcm9030771
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Proanthocyanidins in Ulcerative Colitis in Remission

Abstract: A number of bioactive components of diet are indicated as potential dietary factors for the management of ulcerative colitis, while the recent study conducted in an animal model revealed that proanthocyanidins from grape seeds exert a broadly positive impact. The aim of the study was to verify the influence of dietary proanthocyanidins intake on the symptoms of ulcerative colitis in remission in human subjects. The study was conducted in a group of 55 participants (19 males, 36 females) in remission of ulcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…PAC exert strong antioxidant and anti-inflammatory effects in cellular models, 2,3 and are able to modulate various physiological parameters when consumed as part of the diet, such as increasing mucus production in human patients with ulcerative colitis, and alleviating inflammation in TNBS-induced colitis by inhibiting NF-kB signaling pathways. 4,5 Another consistent outcome of dietary PAC supplementation is the alteration of gut microbiota (GM) composition, which has been observed in both murine and porcine models, with some evidence also from human studies. [6][7][8][9][10] PAC have been shown to increase the abundance of Lactobacilli and Bifidobacterium species, which are commonly associated with a healthy gut environment, as well as increasing levels of fecal short-chain fatty acids (SCFA) such as propionic acid.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…PAC exert strong antioxidant and anti-inflammatory effects in cellular models, 2,3 and are able to modulate various physiological parameters when consumed as part of the diet, such as increasing mucus production in human patients with ulcerative colitis, and alleviating inflammation in TNBS-induced colitis by inhibiting NF-kB signaling pathways. 4,5 Another consistent outcome of dietary PAC supplementation is the alteration of gut microbiota (GM) composition, which has been observed in both murine and porcine models, with some evidence also from human studies. [6][7][8][9][10] PAC have been shown to increase the abundance of Lactobacilli and Bifidobacterium species, which are commonly associated with a healthy gut environment, as well as increasing levels of fecal short-chain fatty acids (SCFA) such as propionic acid.…”
Section: Introductionmentioning
confidence: 92%
“…Numerous studies have demonstrated that PAC play an important role in the regulation of immune function and may offer therapeutic potential towards inflammatory intestinal diseases. PAC exert strong antioxidant and anti‐inflammatory effects in cellular models, 2,3 and are able to modulate various physiological parameters when consumed as part of the diet, such as increasing mucus production in human patients with ulcerative colitis, and alleviating inflammation in TNBS‐induced colitis by inhibiting NF‐kB signaling pathways 4,5 . Another consistent outcome of dietary PAC supplementation is the alteration of gut microbiota (GM) composition, which has been observed in both murine and porcine models, with some evidence also from human studies 6–10 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Lack of abdominal pain was significantly associated with higher dietary daidzein and total isoflavones; however, there was no difference in abdominal pain with higher dietary proanthocyanidins [ 66 ]. Lack of constipation was significantly associated with lower dietary glycitein [ 66 ] and higher dietary proanthocyaninidins were significantly associated with constipation [ 65 ]. Extra virgin olive oil administration resulted in a significant reduction in reports of constipation [ 47 ].…”
Section: (Poly)phenols Inflammatory Bowel Disease and Irritable mentioning
confidence: 99%
“…Numerous studies have demonstrated that PAC play an important role in the regulation of immune function and may offer therapeutic potential towards inflammatory intestinal diseases. PAC exert strong antioxidant and anti-inflammatory effects in cellular models 6,7 , and are able to modulate various physiological parameters when consumed as part of the diet, such as increasing mucus production in human patients with ulcerative colitis, and alleviating inflammation in TNBS-induced colitis by inhibiting NF-kB signaling pathways 8,9 . Another consistent outcome of dietary PAC supplementation is changes in gut microbiota (GM) composition, which has been observed in both murine and porcine models, with some evidence also from human studies [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%